2010
DOI: 10.4161/rna.7.6.13781
|View full text |Cite
|
Sign up to set email alerts
|

The twenty-nine amino acid C-terminal cytoplasmic domain of poliovirus 3AB is critical for nucleic acid chaperone activity

Abstract: Poliovirus 3AB protein is the first picornavirus protein demonstrated to have nucleic acid chaperone activity. Further characterization of 3AB demonstrates that the C-terminal 22 amino acids (3B region (also referred to as VPg), amino acid 88–109) of the protein is required for chaperone activity, as mutations in this region abrogate nucleic acid binding and chaperone function. Protein 3B alone has no chaperone activity as determined by established assays that include the ability to stimulate nucleic acid hybr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…Despite of the numerous commonalities between poliovirus and EV71, the 3AB proteins from these two enteroviruses still exhibited some difference. For example, poliovirus 3AB has been reported to be much more potent than 3B þ7 for RNA chaperone activities (Gangaramani et al, 2010); however, we observed that for EV71, the RNA chaperone activity of wild-type 3AB is only moderately stronger than that of 3Bþ 7 (Fig. 8D).…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…Despite of the numerous commonalities between poliovirus and EV71, the 3AB proteins from these two enteroviruses still exhibited some difference. For example, poliovirus 3AB has been reported to be much more potent than 3B þ7 for RNA chaperone activities (Gangaramani et al, 2010); however, we observed that for EV71, the RNA chaperone activity of wild-type 3AB is only moderately stronger than that of 3Bþ 7 (Fig. 8D).…”
Section: Discussionmentioning
confidence: 61%
“…During the life cycle of EV71, the RNA chaperone activity of 3AB may participate in diverse processes, such as coating and protecting viral genomic RNA, facilitating the formation and/or deformation of vRNA cis-acting elements, vRNA synthesis by RdRp, and translation (Gangaramani et al, 2010). However, due to technical limitations, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations